PROBLEMS ENCOUNTERED BY TEACHER AND STUDENTS IN TEACHING AND LEARNING WRITING DESCRIPTIVE TEXT (RETAIN, 2017)
PROBLEMS ENCOUNTERED BY TEACHER AND STUDENTS IN TEACHING AND LEARNING WRITING DESCRIPTIVE TEXT Stillman Miliam Asan English Department, Faculty of Langauge and Art, State University of Surabaya stillman.asan@gmail.com Prof. Dr. Susanto, M.Pd. English Department, Faculty of Langauge and Art, State University of Surabaya susantoniki@gmail.com Abstrak Menulis merupakan salah satu keterampilan dalam Bahasa Inggris. Menulis adalah tindakan untuk berkomunikasi, cara berbagi sudut pandang, informasi, ide dan pemikirandengan orang lain. Menulis adalah cara untuk memahami Pengalaman untuk diri kita dan orang lain dalam bentuk tertulis. Siswa tidak hanya bisa mengerti tentang gramatikal. Tapi juga belajar cara untuk menyampaikan argumen yang logis serta dapat meyakinkan orang lain. Hal itulah yg menyebabkan keterampilan menulis harus lebih serius untuk dipelajari Penelitian ini menggunakan pendekatan deskriptif kualitatif. Sasarannya yakni 40 siswa dan seorang guru kelas VIII-D SMPN 1 Kintom tahun ajaran 2015/2016.Lembar pengamatan, pedoman wawancara, kuisioner, catatan lapangan dan tes tulis siswa digunakan sebagai alat untuk.mengumpulkan data. Dalam penerapan film sebagai media didalam kelas, siswa mengamati film tersebut pada pertemuan pertama. Kemudian pada pertwmuan selanjutnya siswa mengerjakan tugas dari guru berdasarkan dilm yang telah mereka amati sebelumnya. Pada pertemuan terakhir, guru menganalisa dan menilai tugas siswa. Kemudian peneliti melakukan wawancara pada guru untuk mendapatkan dan mengklarifikasi informasi dan data lebih detail yang tidak jelas saat masa observasi. Selanjutnya, data yang terkumpul dipelajari, diatur dan dianalisa. Akhirnya, dibuat kesimpulan yang sesuai dengan hasil dan pembahasan penelitian. Dari hasil penelitian dapat disimpulkan bahwa implementasi film sebagai media dalam kelas dapat meningkatkan kemampuan siswa untuk mrnulis teks deskriptif. Lebih lanjut, siswa dianjurkan untuk lebih termotivasi pada jenis film lain seperti film anaimasi maupun dokumenter. Seharusnya guru juga mendukung siswa agar lebih terbiasa. Penggunaan pemeriksaan bahasa inggris merupakan hal penting terhadap penilaian siswa karena itu akan memberikan balikan pada siswa sehingga mereka dapat belajar dari kesalahan sebelumnya terutama saat menulis teks deskriptif. Kata Kunci: pendekatan saintifik, aktifitas guru. Abstract Writing is one of English language skills. Writing is a communicative act, a way of sharing views, information, thoughts, or ideas with other people. Writing is one way of making meaning from experience for ourselves and for others in the written form. Through writing students will not only be able to understand about the grammatical but also learn how to make logical argument and how to persuade the other people It makes writing become very crucial to be deeply learned. Moreover, the researcher offered film as media in classroom to answer that problem. Film can the students closer to the object of their writing so they will be easier to get the ideas for their writing. Beside that, the students will be more motivated in writing because Film is an interesting media to learn. This study used descriptivequalitative research. The subjects were 40 students and the English teacherof VIII D in SMP N 1 Kintom in the academic year 2015/2016. The instruments used to collect the data were interview guides, questionnaires, observation checklists, field notes, and the students’ writing test. In the implementation film as media in the classroom, the students watch the film in the first meeting and the next meeting student will do the teacher assignment based on what they watched in the prevoius meeting. In the last meeting, the teacher analyzed and scored their assignment. Then,the teacher was interviewed by the researcher to clarify the more detail information which could not be explained through the observation. Futhermore, the data were familiarized and organized. Finaly, the conclusions were drawn due to the result and the discussion of the research. Learning from the result, it can be concluded that the implementation of film as media in the classroom could improve students’ achievement in writing descriptive text. Furthermore, it is suggested to the students to be more motivated in another genre for learning English such as animated or documentary film. Also teacher should encourage the students to make the students more customary.using english reviewing at students score is important because it can give the feedback to the student, so they can learn for the mistake that thed did, especially when they composed decriptive text. Keywords: scientific approach, teacher’s activities.